Preparation method of aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide

By synergistically using alumina fibers and boron carbide particles in aluminum-bronze composite materials, the problems of complex and high cost of existing copper-based composite materials are solved, and efficient and low-cost preparation methods are realized, which significantly improves the mechanics of the materials performance.

CN119411033APending Publication Date: 2025-02-11HEBEI BOTOU SAFETY TOOLS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411609489.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing copper-based composite materials have complex technology, high production costs and cumbersome processes. It is difficult to improve the hardness and mechanical properties of copper alloy materials at the same time.

Method used

The preparation method of alumina fibers and boron carbide particles to jointly enhance the aluminum bronze composite material is used to form a aluminum bronze composite material with synergistic reinforcement of alumina and boron carbide through the process steps of mixing uniformly, disappearing mold casting and casting copper alloy liquid.

Benefits of technology

It achieves high production efficiency, low cost, firm bonding between alloy particles and substrate, uniform dispersion of particles, significantly improving the comprehensive mechanical properties of the parts, and is suitable for large and complex aluminum-bronze composite parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411033A_ABST
    Figure CN119411033A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide, which belongs to the technical field of mechanical part casting, and comprises the following process steps: uniformly mixing aluminum oxide, boron carbide, an adhesive and EPS (Expandable Polystyrene) beads; putting the mixture of the aluminum oxide and the boron carbide, the adhesive and the EPS beads into a self-made evanescent mode mold, introducing steam, and cooling to obtain an aluminum oxide and boron carbide synergistically reinforced aluminum bronze composite material preform evanescent mode model; and putting the evanescent mode model into a sand mold cavity, pouring copper alloy liquid, and cooling to obtain the aluminum oxide and boron carbide synergistically reinforced aluminum bronze composite material. The production efficiency is high, the cost is low, the alloy particles and the matrix are firmly combined, the particles are uniformly dispersed, the comprehensive mechanical property of the part is remarkably improved, and the method can be used for manufacturing the large aluminum bronze composite material part with the complex shape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mechanical parts casting, and in particular to a method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide. Background Art

[0002] As an important material in the field of mechanical industry, aluminum bronze is widely used in highly corrosive marine environments, such as ship propellers, seawater valves and blades; and it will not produce sparks under strong impact, so it is also one of the main explosion-proof materials in service, and has great application advantages in the petroleum, chemical, coal mining and military industries. Aluminum bronze can generally be divided into simple aluminum bronze (Cu-Al alloy) and complex aluminum bronze (adding Fe, Ni, Mn, Zn, Si and other alloy elements to simple aluminum bronze), among which the A1 element mainly solid dissolves in the α phase to play a strengthening role; the Mn element mainly acts as a deoxidizer to purify; the Fe element can refine the microstructure of the alloy; the Ni element can improve both the mechanical properties and corrosion resistance, so most of the current research and application is complex aluminum bronze.

[0003] In order to further improve the various properties of copper alloys, there are currently two solutions. The first is to change the composition of the alloy and add alloying elements to form a solid solution with copper through solid solution strengthening, or to precipitate the supersaturated solid solution in the form of second phase particles through heat treatment. The strengthening mechanism is precipitation strengthening, also known as dispersion strengthening; the second is to introduce the ceramic reinforcement into the metal matrix through a certain preparation process to form a metal matrix composite material. Its strengthening mechanism is often the result of the combined action of multiple strengthening mechanisms such as dislocation strengthening, dispersion strengthening, and fine grain strengthening. Ceramic reinforcement materials have the characteristics of low cost and wide sources. They can be introduced into the metal matrix by casting, powder metallurgy and other processes, and can also be secondary processed by forging, rolling, extrusion, pulling, and drawing to reduce manufacturing costs. With the continuous development of science and technology, the development of metal matrix composite materials has become an important direction. Its main advantages are: high electrical conductivity, high thermal conductivity, high specific modulus and specific strength, low thermal expansion coefficient, good high temperature stability and creep resistance, good fatigue performance and fracture toughness, no moisture absorption, no aging, and good air tightness. Copper-based composite materials are designed to improve the comprehensive mechanical properties of copper alloys, extend their service life and improve economic benefits by introducing single or multiple ceramic reinforcements into copper and copper alloy matrices.

[0004] Hybrid reinforced copper-based composites refer to the introduction of reinforcing phases of different types, morphologies and scales into the copper alloy matrix, and by controlling the content and ratio of the reinforcing phases, using their different physical characteristics to exert their respective advantages, thereby achieving synergistic effects and obtaining excellent comprehensive performance. In recent years, researchers have prepared a variety of hybrid reinforced copper-based composites, including particle-particle hybrids, fiber-fiber hybrids, particle-fiber hybrids and other forms. Zou Cunlei prepared micron-scale ZrB2 and nano-scale Cu5Zr bipolar particle synergistically reinforced copper-based composites by reaction casting, making them have high strength, high conductivity and high wear resistance. SLLi et al. found that compared with single-phase TiB2 reinforced copper-based composites, dual-scale TiB2 / Cu composites have fewer defects, higher hardness and conductivity. Long Fei prepared carbon nanotubes and TiB2 synergistically reinforced copper-based composites by chemical deposition, powder metallurgy and hot extrusion. The results showed that compared with single-phase reinforcement, hybrid reinforced composites have higher tensile strength, and the synergistic enhancement effect in mechanical properties was confirmed in theoretical calculations and experimental studies. Y. Pan et al. used mixed acid treatment and spark plasma sintering process to prepare carbon nanotubes and nano-alumina synergistically reinforced copper-based composites. The results showed that nano-Al2O3 can be used as an active mixing agent to disperse carbon nanotubes in copper powder, improve the adhesion between carbon nanotubes and copper matrix in the composite material, and the uniformly dispersed nano-Al2O3 and carbon nanotubes can limit grain growth and form a strong bonding interface, thereby improving mechanical properties. SH Liang et al. used a combination of in-situ mixed casting, rolling and annealing to prepare a mixed copper-based composite reinforced with TiB whiskers and TiB2 particles. By controlling the rolling and annealing parameters, the adverse casting defects were eliminated. The uniform distribution of the mixed reinforcement material in the annealed composite material provided good comprehensive performance. (1.0wt.%TiB 2p -0.9wt.%TiB w ) / Cu hybrid composites exhibited higher strength (492 MPa) and higher electrical conductivity (85.5% of international annealed copper standard). Summary of the invention

[0005] In view of the problems of complex preparation technology, high production cost and cumbersome process of existing copper-based composite materials, and the need to further improve the mechanical properties while improving the hardness of copper alloy materials, the purpose of the present invention is to provide a preparation method of aluminum bronze composite materials synergistically reinforced with aluminum oxide and boron carbide.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0007] A method for preparing an aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide comprises the following process steps:

[0008] a. mixing aluminum oxide and boron carbide uniformly to obtain a mixture 1;

[0009] b. Evenly mix the mixture 1, the binder and the EPS particles to obtain the mixture 2;

[0010] c. Mixture 2 is placed in a lost foam mold, steamed, and cooled to obtain a preform lost foam model of aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide; the shape and size of the lost foam mold can be adjusted according to the needs of the parts;

[0011] d. Place the preform lost foam model into a sand mold cavity, pour copper alloy liquid, and cool to obtain an aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide.

[0012] Preferably, the alumina in step a is Al2O3, the Al2O3 fiber size is 10-20 um in diameter and 0.3-0.7 mm in length; the particle size of boron carbide B4C is 4-15 μm.

[0013] Preferably, the mixing conditions in step a are: stirring at 150-180 r / min for 200-250 s.

[0014] Preferably, in step b, the volume fraction of the second mixture is: Al2O 3f 1-3 parts of fiber, 1-3 parts of B4C particles, 92-96 parts of EPS particles, and 2 parts of binder.

[0015] Preferably, the mixing conditions in step b are: stirring at 150-180 r / min for 300-350 s;

[0016] The binder is a type A organic binder, which is obtained by dissolving a composition consisting of phenolic resin and rosin in a mass ratio of 1.8-2.2:1 into anhydrous ethanol, and the concentration of the composition in the binder is 0.08-0.12 g / ml.

[0017] Preferably, in step c, the hot steam temperature is 120° C., the air pressure is 0.15 MPa, and the ventilation and pressure holding time in the mold is 2-5 min.

[0018] Preferably, in the cooling step in step c, cooling water is used to cool the mixture to 50° C. or below.

[0019] Preferably, step d is specifically as follows: pouring temperature is 1220-1260°C, heat preservation is performed for 2-3 hours after pouring, cooling, box turning, and sand removal are performed to obtain aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide. During the pouring of aluminum bronze alloy liquid, the EPS in the model is volatilized, and the aluminum bronze alloy liquid fills the cavity.

[0020] Preferably, the chemical composition and mass percentage content of the aluminum bronze poured in step d are Al: 10-12%, Ni: 4.0-6.0%, Fe: 3.0-5.8%, Zn: 0.5-2.0%, and Cu: balance.

[0021] Preferably, in step d, the temperature is naturally cooled to 350-400°C.

[0022] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are as follows:

[0023] The preparation method of the aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide provided by the present invention has high production efficiency and low cost, and the alloy particles are firmly bonded to the matrix, the particles are evenly dispersed, and the comprehensive mechanical properties of the parts are significantly improved. This method can be used to produce large aluminum bronze composite parts with complex shapes.

[0024] The present invention adopts raw materials such as aluminum oxide fiber, boron carbide particles, and EPS beads. The aluminum oxide fiber and boron carbide particles are evenly distributed in the copper matrix, which plays a role of dispersion strengthening. At the same time, the boron carbide particles, as a hard phase, share the external load and reduce the wear effect on the copper matrix. The aluminum oxide fiber can enhance the hardness of the copper matrix and improve the toughness of the alloy. The EPS beads have a certain compressive strength, ensuring that the aluminum oxide fiber and the boron carbide particles do not collapse and agglomerate before being mixed into the copper liquid. At the same time, they have good volatility, ensuring that they can be quickly gasified and disappear after acting with the high-temperature copper liquid.

[0025] The volume ratio of alumina fiber, boron carbide particles, EPS beads and binder enables the alumina fiber and boron carbide particles in the preformed pattern to be well supported by the EPS beads, and the alumina fiber and boron carbide particles can be evenly distributed in the space dominated by the EPS beads without any segregation.

[0026] The preparation method of the aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide provided by the invention has strong operability, low production cost, high production efficiency, and is easy to realize industrial production, especially improving the mechanical properties of target parts, extending the service life of target parts, and saving energy and reducing consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A flow chart of a method for preparing alumina and boron carbide synergistically reinforced aluminum bronze composite material;

[0028] Figure 2 This is the microstructure diagram of aluminum bronze matrix;

[0029] Figure 3 For Example 2 (Al2O 3f +B4C p ) / Cu composite microstructure diagram;

[0030] Figure 4 For Example 2 (Al2O 3f +B4C p ) / Cu composite X-ray diffraction pattern;

[0031] Figure 5 For Example 2 (Al2O 3f +B4C p ) / Cu composite material impact fracture SEM morphology;

[0032] Figure 6 For Example 2 (Al2O 3f +B4C p ) / Cu composite material worn surface SEM morphology. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is described in detail below in conjunction with specific implementation methods.

[0034] In this application, Al2O 3f Al2O3 fiber; B4C p It is a particle of B4C.

[0035] Example 1

[0036] like Figure 1 As shown, a method for preparing an aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide comprises the following process steps:

[0037] a. Alumina is Al2O3 fiber, the size of Al2O3 fiber is 10-20um in diameter and 0.3-0.7mm in length, and the particle size of B4C is 4-15μm. The mixing conditions in step a are: stirring at 180r / min for 200s.

[0038] b. The volume proportions of alumina, boron carbide, binder, and EPS are: 1 part of Al2O3 fiber, 1 part of B4C particles, 96 parts of EPS beads, and 2 parts of binder. The binder is obtained by dissolving a composition consisting of phenolic resin and rosin in a mass ratio of 2.2:1 into anhydrous ethanol, and the concentration of the composition in the binder is 0.12 g / ml.

[0039] The mixture of aluminum oxide and boron carbide + binder + EPS is mixed evenly. The mixing conditions of the mixture of aluminum oxide and boron carbide + binder + EPS are: stirring at 180 r / min for 200 s.

[0040] c. The mixture of alumina and boron carbide + binder + EPS was placed in a homemade lost foam mold, steamed, and cooled to 28°C to obtain a lost foam model of an aluminum bronze composite material preform synergistically reinforced with alumina and boron carbide. The hot steam temperature was 120°C, the air pressure was 0.15 MPa, and the ventilation and pressure holding time in the mold was 5 minutes.

[0041] d. Place the lost foam model into the sand mold cavity, pour the copper alloy liquid, and cool to 360°C to obtain an aluminum-bronze composite material synergistically reinforced with aluminum oxide and boron carbide. The pouring temperature is 1220-1260°C. After pouring, keep warm for 2 hours, turn the box over, and remove the sand to obtain an aluminum-bronze composite material casting synergistically reinforced with aluminum oxide and boron carbide.

[0042] The chemical composition and mass percentage of the cast aluminum bronze are Al: 10%, Ni: 6.0%, Fe:

[0043] 3.8%, Zn: 2.0%, Cu: balance.

[0044] Example 2

[0045] like Figure 1 As shown, a method for preparing an aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide comprises the following process steps:

[0046] a. Alumina is Al2O 3f The fiber size of Al2O3 fiber is 10-20 μm in diameter and 0.3-0.7 mm in length, and the particle size of B4C is 4-15 μm. The mixing condition in step a is: stirring at 150 r / min for 250 s.

[0047] b. The volume proportions of alumina, boron carbide, binder, and EPS are: 2 parts of Al2O3 fiber, 2 parts of B4C particles, 94 parts of EPS beads, and 2 parts of binder. The binder is prepared by dissolving a composition consisting of phenolic resin and rosin in a mass ratio of 1.8:1 into anhydrous ethanol, and the concentration of the composition in the binder is 0.08 g / ml.

[0048] The mixture of aluminum oxide and boron carbide + binder + EPS is mixed evenly. The mixing conditions of the mixture of aluminum oxide and boron carbide + binder + EPS are: stirring at 150 r / min for 200 s.

[0049] c. The mixture of alumina and boron carbide + binder + EPS mixture is placed in a homemade lost foam mold, steamed, and cooled to 50°C to obtain a lost foam model of an aluminum bronze composite material preform synergistically reinforced with alumina and boron carbide. The hot steam temperature is 120°C, the air pressure is 0.15 MPa, and the ventilation and pressure holding time in the mold is 2 minutes.

[0050] d. Place the lost foam model into the sand mold cavity, pour the copper alloy liquid, cool to 350°C to obtain an aluminum-bronze composite material synergistically reinforced with aluminum oxide and boron carbide, the pouring temperature is 1220-1260°C, keep warm for 2.5 hours after pouring, turn the box over, and remove the sand to obtain an aluminum-bronze composite material casting synergistically reinforced with aluminum oxide and boron carbide.

[0051] The chemical composition of the cast aluminum bronze and its mass percentage content are Al: 11%, Ni: 4.0%, Fe: 5.8%, Zn: 1.5%, Cu: balance.

[0052] (Al2O 3f +B4C p ) / Cu composite microstructure, X-ray diffraction, impact fracture SEM morphology and wear surface SEM morphology are shown in Figure 3-6 .

[0053] Example 3

[0054] like Figure 1 As shown, a method for preparing an aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide comprises the following process steps:

[0055] a. Alumina is Al2O3, Al2O3 fiber size is 10-20um in diameter, 0.3-0.7mm in length, B4C particle size is 4-15μm. The mixing conditions in step a are: stirring at 160r / min for 200-230s.

[0056] b. The volume proportions of alumina, boron carbide, binder, and EPS are: 3 parts of Al2O3 fiber, 3 parts of B4C particles, 92 parts of EPS beads, and 2 parts of binder. The binder is prepared by dissolving a composition consisting of phenolic resin and rosin in a mass ratio of 2.0:1 into anhydrous ethanol, and the concentration of the composition in the binder is 0.10 g / ml.

[0057] The mixture of aluminum oxide and boron carbide + binder + EPS is mixed evenly. The mixing conditions of the mixture of aluminum oxide and boron carbide + binder + EPS are: stirring at 160 r / min for 230 s.

[0058] c. The mixture of alumina and boron carbide + binder + EPS mixture is placed in a homemade lost foam mold, steamed, and cooled to 30°C to obtain a lost foam model of an aluminum bronze composite material preform synergistically reinforced with alumina and boron carbide. The hot steam temperature is 120°C, the air pressure is 0.15 MPa, and the ventilation and pressure holding time in the mold is 4 minutes.

[0059] d. Place the lost foam model into the sand mold cavity, pour the copper alloy liquid, and cool to 400°C to obtain an aluminum-bronze composite material synergistically reinforced with aluminum oxide and boron carbide. The pouring temperature is 1220-1260°C. After pouring, keep warm for 3 hours, turn the box over, and remove the sand to obtain an aluminum-bronze composite casting synergistically reinforced with aluminum oxide and boron carbide.

[0060] The chemical composition and mass percentage of the cast aluminum bronze are Al: 12%, Ni: 5.0%, Fe:

[0061] 3.0%, Zn: 0.5%, Cu: balance

[0062] Comparative Example 1

[0063] a. Use clay sand for modeling;

[0064] b. Melting aluminum bronze;

[0065] c. pouring the aluminum-bronze alloy liquid into the prepared clay sand mold cavity, solidifying, and cooling to obtain an aluminum-bronze alloy test block;

[0066] The chemical composition and mass percentage of the cast aluminum bronze are Al: 10%, Ni: 6.0%, Fe: 3.8%, Zn: 2.0%, Cu: balance. The casting temperature is 1220-1260°C.

[0067] Samples were cut from the above test blocks, and their properties were measured and their metallographic structures were observed. The experimental data, macroscopic and microscopic structures obtained are shown in Tables 1 and 2:

[0068] Table 1 Wear test parameters

[0069]

[0070] Table 2 Wear resistance data of aluminum bronze material test block

[0071] project Wear amount / g Relative wear resistance Matrix 0.1525 --------------

[0072] The microstructure of the comparative example Figure 2 shown.

[0073] Samples were cut from the aluminum-bronze composite material reinforced with aluminum oxide and boron carbide in the embodiment, and their properties were measured and their metallographic structures were observed. The experimental data, macroscopic and microscopic structures obtained are shown in Tables 3 and 4:

[0074] Table 3 Test block wear data

[0075] project Wear amount / g Relative wear resistance Example 1 0.1101 1.385 Example 2 0.1051 1.4510 Example 3 0.1190 1.2815 Comparative Example 1 0.1525 --------------

[0076] Table 4 Test block properties

[0077] project <![CDATA[Impact performance / Jcm -2 > Vickers hardness Example 1 96 238 Example 2 101 270 Example 3 86 264 Comparative Example 1 82 201

[0078] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide, characterized in that: The following steps are involved: a. uniformly mixing aluminum oxide and boron carbide to obtain a mixture 1; b. Evenly mix the mixture 1, the binder and the EPS particles to obtain the mixture 2; c. putting the second mixture into a lost foam mold, passing steam, and cooling to obtain a lost foam model of a preform of an aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide; d. Place the preform lost foam model into a sand mold cavity, pour copper alloy liquid, and cool to obtain an aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide.

2. The method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide according to claim 1, characterized in that: The alumina in step a is Al2O3 fiber, the size of the Al2O3 fiber is 10-20um in diameter and 0.3-0.7mm in length; the particle size of boron carbide B4C is 4-15μm.

3. The method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide according to claim 1, characterized in that: The mixing conditions in step a are: stirring at 150-180 r / min for 200-250 s.

4. The method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide according to claim 1, characterized in that: In step b, the volume proportions of the second mixture are: 1-3 parts of Al2O3 fibers, 1-3 parts of B4C particles, 92-96 parts of EPS particles, and 2 parts of binder.

5. The method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide according to claim 1, characterized in that: The mixing conditions in step b are: stirring at 150-180 r / min for 300-350 s; The binder is a type A organic binder, which is obtained by dissolving a composition consisting of phenolic resin and rosin in a mass ratio of 1.8-2.2:1 into anhydrous ethanol, and the concentration of the composition in the binder is 0.08-0.12 g / ml.

6. The method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide according to claim 1, characterized in that: In step c, the hot steam temperature is 120° C., the air pressure is 0.15 MPa, and the ventilation and pressure holding time in the mold is 2-5 minutes.

7. The method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide according to claim 1, characterized in that: In step c, the cooling step is cooled to 50° C. or below by cooling water.

8. The method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide according to claim 1, characterized in that: Step d is specifically as follows: pouring temperature is 1220-1260° C., heat preservation is performed for 2-3 hours after pouring, cooling, box turning, and sand removal are performed to obtain an aluminum bronze composite material synergistically reinforced with aluminum oxide and boron carbide.

9. The method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide according to claim 1, characterized in that: The chemical composition and mass percentage content of the aluminum bronze poured in step d are Al: 10-12%, Ni: 4.0-6.0%, Fe: 3.0-5.8%, Zn: 0.5-2.0%, and Cu: balance.

10. The method for preparing an aluminum bronze composite material synergistically reinforced by aluminum oxide and boron carbide according to claim 1, characterized in that: In step d, the temperature is naturally cooled to 350-400°C.